Perbanyakan Padi Fl Interspesifik untuk Bahan Silang Balik (Back Cross) - Syukur, M.; Aswidinnoor, H.; Suharsono, , (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2003)
A lot of plant materials are needed for successful back cross program of interspecific FI rice to their recurrent parents. Multiplication of the steril FI plants through tiller propagation is not adequate. The research aims to develop technique of vegetatif multiplication of interspesific hybrid rice utilizing nodal segments. In the vegetatif multiplication experiment, several factors were examined as treatments: nutrition culture (MS, Yoshida, and water), stum position (first, second and third) and growth media (vermiculite, husk charcoal, and sand). The plant materials are interspecific FI rice i.e. Ranah Sanra (genom AA) x O. officinalis 100870 (genom CC), Hawara Bunar (genom AA) x O. Punctata 9101411 (genom BB), Grogol (genom AA) x O. punctata 9101411 (genom BB), CT 6510-24-1-3 (genom AA) x O. malamphuzaensis 100957 (genom BBCC). Results of the study indicated that MS and Yoshida nutrition, stum without sheath, base of stum and sand media gave better growth more than other treatments. Key words: Vegetatif multiplication, FI interspecific